Experimental and numerical investigation of Helmholtz resonators and perforated liners as attenuation devices in industrial gas turbine combustors. (1st July 2015) - Houston, B.; Wang, J.; Qin, Q.; Rubini, P.
Highlights: Helmholtz resonators and perforated panel's attenuation properties are measured. CFD simulations of Helmholtz resonators are validated against measurements. A porous model for CFD simulation of perforated plates is presented. Existing analytical models are compared with CFD models and measured data. CFD methods are shown to improve the prediction of resultant attenuation. Abstract: This paper reports upon developments in the simulation of the passive control of combustion dynamics in industrial gas turbines using acoustic attenuation devices such as Helmholtz resonators and perforated liners. Combustion instability in gas turbine combustors may, if uncontrolled, lead to large-amplitude pressure fluctuations, with consequent serious mechanical problems in the gas turbine combustor system. Perforated combustor walls and Helmholtz resonators are two commonly used passive instability control devices. However, experimental design of the noise attenuation device is time-consuming and calls for expensive trial and error practice. Despite significant advances over recent decades, the ability of Computational Fluid Dynamics to predict the attenuation of pressure fluctuations by these instability control devices is still not well validated. In this paper, the attenuation of pressure fluctuations by a group of multi-perforated panel absorbers and Helmholtz resonators are investigated both by experiment and computational simulation. It is demonstrated that CFD can predict the noise attenuation from Helmholtz resonators with good accuracy. A porous material model is modified to represent a multi-perforated panel and this perforated wall representation approach is demonstrated to be able to accurately predict the pressure fluctuation attenuation effect of perforated panels. This work demonstrates the applicability of CFD in gas turbine combustion instability control device design.